Group Discussion Method In Improving English Language Skills For Students of STIKOM UyelindoKupang - Heni, Heni (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
English courses at STIKOM Uyelindo are given in semesters 1 and 2. In implementing English courses at STIKOM Uyelindo Kupang, there are still several obstacles in the teaching and learning process. One of them is the lack of absorption of English language material by students. This is because the method used in teaching is still teacher centered. The lecturer delivers the material and students listen and take notes. After delivering the material, the lecturer provides students with several exercises to do. During English lectures using this method, the results achieved were not optimal. Students' abilities in five English skills are less than optimal. The five skills referred to include: reading, writing, listening, translating, and speaking. In studying, a student is usually supported by several aspects to achieve maximum results. Several aspects that support learning include students being able to collaborate with other students. Apart from being influenced by learning methods, student learning outcomes are also influenced by student participation. The results obtained from the research are that there is a correlation between the group discussion method and increased student learning achievement in English courses, in reading, writing, listening and speaking skills. The correlation between group discussions and student test results in class A is 0.60 which means that the two variables have a strong relationship, while in class B the correlation between group discussions and student test results in class B is 0.71 which means that The two variables have a very strong relationship.